Analysis of the way of pretreatment before transportation of palm biomass fuel - Niu, Yitong; Korneev, Andrei (Sustainable Engineering and Innovation, 2022)
With the increasing concern about the environment, renewable energy development is imminent, and biomass utilization is an essential part of it. In many regions (e.g., Southeast Asia), palm kernels are a very economical feedstock for biomass energy production. However, the collection and transportation of palm kernels are complicated, which is not conducive to the further development of this industry. This paper analyzes the current situation of collection and transportation of palm kernels in Southeast Asian countries using basic analysis methods. Meanwhile, the characteristics of palm fruit bunches as biomass fuel and its transportation and handling methods are briefly introduced and analyzed concerning the fuel demand of biomass power generation projects. The shortcomings of the current methods were identified, and relevant directions for improvement were proposed. It is hoped that it can improve the transportation efficiency of palm fruit bunches as a feedstock for biomass power generation and provide a reference basis for the collection and transportation of palm fruit bunches biomass.